Incidence of Domestic Violence Among Literate Married Adults in Ilorin Metropolis, Kwara State - Adeboye, Adenike Abiola; Agubosi, Lydia Akunna; Olaifa, Adeseko Sunday; Akintunde, Karimot .Y. (International Journal of Educational Management, 2021)
Domestic violence is rampant among Christians and non-Christians, rich and poor, male and female, quite and aggressive individual, young and old, high income group and low income group. Therefore, this study investigated the incidence of domestic violence among literate married adults in Ilorin metropolis, Kwara state. The moderating variables considered are age, gender and family type. The research design used for this study was descriptive survey and simple random sampling technique was used to select the target population. Two hundred (200) respondents were randomly selected from the literate married adults in Ilorin metropolis. The main instrument used was researchers' self-designed questionnaire tagged “Incidence of Domestic Violence Questionnaire”(IDVQ) which consisted of section A and B. Section A elicited information on demographic data while section B consisted of 20 items on incidence of domestic violence. One research question was 13 raised and three null hypotheses were formulated for this study. All hypotheses were tested and accepted at 0.05 level of significance. Results revealed that there are no significant differences in the incidence of domestic violence on the basis of age, gender and family type. It was recommended that psychologists, counsellors and marriage counsellors should initiate vigorous campaign against domestic violence. Counsellors should assist in reconstructing the married couples' cognitive disposition by organizing seminars, symposium and marital counselling.Association of Professional Counsellors of Nigeria (APROCON) should build up enlightenment programmes through workshop and seminars for married adults periodically.